A Small Molecule CXCR4 Inhibitor that Blocks T Cell Line–tropic HIV-1 Infection - Murakami, Tsutomu (The Rockefeller University Press, 1997)
Several members of the chemokine receptor family have been shown to function in association with CD4 to permit human immunodeficiency virus type 1 (HIV-1) entry and infection. The CXC chemokine receptor CXCR4/fusin is a receptor for pre–B cell growth stimulating factor (PBSF)/stromal cell–derived factor 1 (SDF-1) and serves as a coreceptor for the entry of T cell line–tropic HIV-1 strains. Thus, the development of CXCR4 antagonists or agonists may be useful in the treatment of HIV-1 infection. T22 ([Tyr(5,12),Lys(7)]-polyphemusin II) is a synthesized peptide that consists of 18 amino acid residues and an analogue of polyphemusin II isolated from the hemocyte debris of American horseshoe crabs (Limulus polyphemus). T22 was found to specifically inhibit the ability of T cell line–tropic HIV-1 to induce cell fusion and infect the cell lines transfected with CXCR4 and CD4 or peripheral blood mononuclear cells. In addition, T22 inhibited Ca(2+) mobilization induced by pre–B cell growth stimulating factor (PBSF)/SDF-1 stimulation through CXCR4. Thus, T22 is a small molecule CXCR4 inhibitor that blocks T cell line–tropic HIV-1 entry into target cells.